Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1016/0950-3528(93)90002-a
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of alcoholic liver disease

Abstract: This article describes the various forms of alcoholic liver disease (ALD), with particular emphasis on cirrhosis, the form of liver disease that often is most associated with alcohol abuse and about which the most information is available. Epidemiological research has evaluated the prevalence of ALD and the factors that often contribute to the disease. Although the most potent factor in ALD is the excessive consumption of alcoholic beverages, gender and ethnic differences also account for some important variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 111 publications
0
19
0
Order By: Relevance
“…Indeed, native livers from hepatitis C-infected patients here and in other studies often showed morphology of chronic hepatitis rather than alcohol injury ( Table 1), suggesting that alcohol had exacerbated viral damage rather than the other way around (19,20). In alcoholics, the presence and severity of clinical liver disease correlate with hepatitis C seropositivity (17,21); alcohol may increase hepatitis C replication and liver injury (22) and accelerate fibrosis (23). Hence, such cases might be better regarded as a subgroup of the coexistent diagnosis (hepatitis C) rather than alcohol liver disease, especially when considering the impact of pretransplant diagnosis on graft outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, native livers from hepatitis C-infected patients here and in other studies often showed morphology of chronic hepatitis rather than alcohol injury ( Table 1), suggesting that alcohol had exacerbated viral damage rather than the other way around (19,20). In alcoholics, the presence and severity of clinical liver disease correlate with hepatitis C seropositivity (17,21); alcohol may increase hepatitis C replication and liver injury (22) and accelerate fibrosis (23). Hence, such cases might be better regarded as a subgroup of the coexistent diagnosis (hepatitis C) rather than alcohol liver disease, especially when considering the impact of pretransplant diagnosis on graft outcome.…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that around two billion people drink ethanol on a regular basis . Ethanol consumption has long been recognized as a major cause of liver disease, but it can also affect the gastrointestinal (GI) tract and is associated with the development of oral, esophageal, and colorectal cancers . Ethanol as well as its metabolites can cause damage that includes decreased intestinal motility and cytotoxic and mutagenic effects .…”
Section: Introductionmentioning
confidence: 99%
“…However, several observations suggest that other factors should interact with alcohol consumption in causing liver damage. [18][19][20] In alcoholics, liver histology is normal in 5% to 25% of biopsies and 18% of autopsy findings, 21 and cirrhosis develops at a low yearly incidence rate of around 2%. 16 Thus, only 10% to 25% of alcoholics will suffer from cirrhosis during their life.…”
mentioning
confidence: 99%